Problem-Solving Skills Among 21st-Century Learners Toward Creativity and Innovation Ideas - Adeoye, Moses Adeleke; Jimoh, Hassanat Abdullateef (Universitas Pendidikan Ganesha, 2023)
In the 21st century, innovation and creativity are becoming increasingly important for success in both academic and professional settings. To promote innovation and creativity, it is essential to prioritize the development of problem-solving skills among learners. This study aims to analyze the problem-solving skills in promoting innovation and creativity and provides a key theoretical model for developing these skills. The method used in this research is Systematic Literature Review. Researchers collected journal articles from Google Scholar, Research Gate, SINTA, Scopus, and Web of Science. The result found problem-solving skills enable learners to analyze complex problems, develop creative solutions, and implement those solutions effectively. One key theoretical model that supports problem-solving skills is the Creative Problem Solving (CPS) model. The aCPS model consists of six stages: understanding the problem, generating ideas, developing solutions, planning for action, taking action, and evaluating results. Prioritizing problem-solving skills among learners has been linked to academic achievement, success in the workforce and higher levels of innovation and creativity.